Sliding mode control for 2 degrees of freedom upper limb rehabilitation robotics system under uncertainties - Ahmed, Syed Faiz; Raza, Yarooq; T. Hussian, Abadal Salam; Joyo, M. Kamran; Shah, Asadullah (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
rehabilitation of patients suffering from post-stroke injuries via robots in now adapted world widely. The aim of this therapy is to restore and improve the dysfunction and the performance of the affected limbs doing repetitive tasks with the help of rehabilitation robots, as robots are best way to perform repetitive task without and monotony failure, Control of these rehabilitation robots is an important part to consider because of nonlinear sliding mode controller (SMC) for controlling a 2 degrees of freedom (DOF) upper limb robotic manipulators. Sliding mode control is able to handle system uncertainties and parametric changes, One drawback of using SMC is high frequency osculations called layer techniques. This chattering can be reduced by using boundary layer techniques. Experiments have been carried our under perturbed conditions and results have been shown that SMC performance well and remain stable and thus proves to robust controller for upper limb robotic manipulator.